Simulation of muscle and adipose tissue deformation in the passive human pharynx. Issue 7 (18th May 2016) - Carrigy, Nicholas B.; Carey, Jason P.; Martin, Andrew R.; Remmers, John E.; Zareian, Ali; Topor, Zbigniew; Grosse, Joshua; Noga, Michelle; Finlay, Warren H.
Abstract : Quantifying the contribution of passive mechanical deformation in the human pharynx to upper airway collapse is fundamental to understanding the competing biomechanical processes that maintain airway patency. This study uses finite element analysis to examine deformation in the passive human pharynx using an intricate 3D anatomical model based on computed tomography scan images. Linear elastic properties are assigned to bone, cartilage, ligament, tendon, and membrane structures based on a survey of values reported in the literature. Velopharyngeal and oropharyngeal cross-sectional area versus airway pressure slopes are determined as functions of Young's moduli of muscle and adipose tissue. In vivo pharyngeal mechanics for small deformations near atmospheric pressure are matched by altering Young's moduli of muscle and adipose tissue. The results indicate that Young's moduli ranging from 0.33 to 14 kPa for muscle and adipose tissue matched the in vivo range of area versus pressure slopes. The developed anatomical model and determined Young's moduli range are expected to be useful as a starting point for more complex simulations of human upper airway collapse and obstructive sleep apnea therapy.